2018
DOI: 10.1097/jcn.0000000000000507
|View full text |Cite
|
Sign up to set email alerts
|

Portable Bladder Ultrasound Reduces Incidence of Urinary Tract Infection and Shortens Hospital Length of Stay in Patients With Acute Ischemic Stroke

Abstract: Background:Urinary tract infection (UTI) during acute ischemic stroke is associated with a longer hospital length of stay and unfavorable functional outcomes.Objective:We investigated the benefits of portable bladder ultrasound (PBU) scanning during acute ischemic stroke.Methods:We retrospectively reviewed patients with acute ischemic stroke from January 2011 to February 2017. Patients were divided into group 1 (PBU not available) and group 2 (PBU available), before or after the split date, April 9, 2014. Port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
(29 reference statements)
1
14
0
6
Order By: Relevance
“…Univariate and multivariate analysis showed that increased age was associated with UTI in this study, which is consistent with previous findings suggesting that age (>75 years) is a factor associated with UTI in stroke patients [2,16,17]. With the increase of age, the anatomical barrier and physiological function of the urinary system gradually decline.…”
Section: Discussionsupporting
confidence: 92%
“…Univariate and multivariate analysis showed that increased age was associated with UTI in this study, which is consistent with previous findings suggesting that age (>75 years) is a factor associated with UTI in stroke patients [2,16,17]. With the increase of age, the anatomical barrier and physiological function of the urinary system gradually decline.…”
Section: Discussionsupporting
confidence: 92%
“…Despite lowering UTI frequency, prophylactic antibiotics did not benefit functional outcome or reduce mortality in clinical trials similar to SAP [ 46 ]. Risk factors include catheter use, incontinence, and post-void residual urine volume [ 47 ], though high rates of UTI have been reported in patient cohorts both with (50%) and without (24%) indwelling catheters [ 48 ]. Programs that prompted routine assessment, stop orders, or early removal reduced catheter duration and incidence of UTI [ 49 ], as did measuring post-void urine volume with portable bladder ultrasound [ 47 ].…”
Section: Stroke-induced Immunodepressionmentioning
confidence: 99%
“…Risk factors include catheter use, incontinence, and post-void residual urine volume [ 47 ], though high rates of UTI have been reported in patient cohorts both with (50%) and without (24%) indwelling catheters [ 48 ]. Programs that prompted routine assessment, stop orders, or early removal reduced catheter duration and incidence of UTI [ 49 ], as did measuring post-void urine volume with portable bladder ultrasound [ 47 ]. Antimicrobial or antibiotic-impregnated catheters have been shown to delay or prevent bacteriuria, but evidence of UTI reduction is scarce [ 50 ] and highlights immune system complexity after stroke.…”
Section: Stroke-induced Immunodepressionmentioning
confidence: 99%
“…Por otro lado, tampoco se han encontrado diferencias en cuanto a la incidencia de ITU posterior al sondaje vesical en ambos grupos, dado que solo disponemos de los sondajes, y no del total de pacientes ingresados. Los resultados obtenidos en cuanto a la duración del ingreso, siguen la línea de estudios previos en pacientes quirúrgicos (31,32) .…”
Section: Discussionunclassified